Rekonstruksi Paradigma Kurikulum dalam Ekosistem Digital: Analisis Evolusioner Pendidikan dari Era Industrialisasi - Prety Gracia Dara; Maria Indriani Sesfao (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
The development of digital technology related to the curriculum, previously rooted in the logic of the industrial era, tends to emphasize standardization, linearity, and knowledge transmission, making it less relevant in facing the complexity and dynamics of the digital ecosystem. This study aims to reconstruct the curriculum paradigm in the context of the digital ecosystem through an evolutionary analysis of education from the industrial era to the digital era, using qualitative methods whose data collection is obtained from the latest and relevant scientific literature. Data analysis is carried out through stages of reduction, thematic categorization, and conceptual synthesis to identify shifts in the curriculum paradigm and their implications for educational practice. The results of the study indicate that the reconstruction of the curriculum paradigm in the digital ecosystem requires systemic changes, encompassing epistemological, pedagogical, and structural dimensions. The curriculum needs to be directed at the development of 21st-century competencies, learner-centered learning, and authentic and reflective assessment design. In addition, the role of teachers as learning facilitators and designers of learning experiences is a key factor in the effective implementation of the digital curriculum. This article concludes that an adaptive, contextual, and humanistic curriculum is a primary prerequisite for the sustainability of education in the digital era. These findings are expected to provide theoretical contributions to curriculum studies and serve as a reference for developing educational policies and practices that are responsive to changing times.